Analyzing Main Topics Regarding The Electronic Information and Transaction Act in Instagram Using Latent Dirichlet Allocation - Kresnawan, Hans; Felle, Sola Graciana; Mokay, Hanna Gloria; Rakhmawati, Nur Aini (Data Science: Journal of Computing and Applied Informatics, 2021)
Indonesia is currently experiencing its fourth industrial revolution in the 21st century. With the introduction of the internet, Indonesia is expected to gain more than a hundred billion US Dollars and twenty-six million job openings by 2030. The rising usage of information technology prompts regulators to develop The Electronic Information Transaction Act to protect the populace from cybercrime. However, the law attracts numerous criticism due to its vague interpretation. This resulted in numerous arrests of innocents throughout Indonesia. Thus, the public is trying to voice their opinions on social media for the sake of preventing any more cases in the future. The usage of Latent Dirichlet Allocation could provide numerous benefits for this research. The separation between latent topics among random mixtures helps to identify the common ground and correlation between each post. These latent topics will be elaborated with a sample post to provide insights and expectations of the public towards the law.